Collaborative web extensions: a P2P approach - Gonzalez, Rodolfo (2021)
Web extensions are powerful software artifacts that allow end-users toadapt and enrich a website. These extensions run on the user´s web browser as asingle-user software that manipulates available third-party web contents. Manyof them offer some collaborative features that depend on a web application. Theneed of two co-depending software artifacts (the web application as back-end andthe web extensions as front-end) increases complexity, making the system harderto develop and maintain. In this paper we tackle this problem by proposing a P2Papproach to build collaborative web extensions. The approach involves amiddleware and a framework. On the one hand, the middleware serves to managethe resources offered by the browser so multiple P2P extensions can coexist. Itensures that the overall performance of the browser is not degraded by thecollaborative web extension. On the other hand, the proposed framework isintended to allow developers without experience in P2P to create collaborativeweb extensions on top of the middleware. This paper discusses the mainchallenges of building P2P web extensions, presents the approach, and two casestudies focused on the use of the framework for inexperienced developers.